COPASI and its applications in biotechnology - Bergmann, Frank T.; Kummer, Ursula; Pahle, Jürgen; Sahle, Sven (Journal of biotechnology, 2017)
COPASI is software used for the creation, modification, simulation and computational analysis of kinetic models in various fields. It is open-source, available for all major platforms and provides a user-friendly graphical user interface, but is also controllable via the command line and scripting languages. These are likely reasons for its wide acceptance. We begin this review with a short introduction describing the general approaches and techniques used in computational modeling in the biosciences. Next we introduce the COPASI package, and its capabilities, before looking at typical applications of COPASI in biotechnology.
Gesehen am 09.05.2018